The Role Of Moringa Leaf Extract (Moringa Oleifera) On Interleukin-10 Levels In Chronic Inflammation Of The Dermis Of White Wistar Rats (Rattus Norvegicus) - Nurwinda Enni Rosyidah; Theresia Indah Budhy (Jurnal Biosains Pascasarjana, 2022)
Traumatic injury can cause chronic inflammation that lasts several months to years. Interleukin-10 plays an important role in the repair of tissue fibrosis and accelerates wound healing. The active compounds of secondary metabolites in Moringa leaves include flavonoids, saponins, alkaloids, and tannins that can accelerate wound closure and act as anti-inflammatory effect to help vasoconstriction in blood vessels so as to minimize signs of inflammation. The aim of this study was to analyze the role of Moringa leaf extract on Interleukin-10 levels in chronic dermis inflammation. This study used a true experimental research with a post-test only control group design. This experimental procedure using 20 male Wistar rats, aging 2-3 months, weighing 150-200 grams and divided into four groups, a negative control group and experiment group with treatment of Moringa leaf extract at concentration of 5%, 10% and 15%. The extract was administered for 3 days after the creation of chronic inflammation in the dermis. Blood serum were taken after 3 days administration of Moringa leaf extract. Analysis using Kruskal Wallis with 5% of error rate. The results showed p=0.040 (p<0.005), which means interleukin-10 levels in experiment group with treatment of Moringa leaf extract were significantly increased. The leaf extract of Moringa oleifera had a role in increasing Interleukin-10 levels in chronic dermis inflammation of male white Wistar rats (Rattus norvegicus) with the best concentration of 15%.